2015
DOI: 10.1039/c4nr07341j
|View full text |Cite
|
Sign up to set email alerts
|

A Stillinger–Weber potential for single-layered black phosphorus, and the importance of cross-pucker interactions for a negative Poisson's ratio and edge stress-induced bending

Abstract: The distinguishing structural feature of single-layer black phosphorus is its puckered structure, which leads to many novel physical properties. In this work, we first present a new parameterization of the Stillinger-Weber potential for single-layer black phosphorus. In doing so, we reveal the importance of a cross-pucker interaction term in capturing its unique mechanical properties, such as a negative Poisson's ratio. In particular, we show that the cross-pucker interaction enables the pucker to act as a re-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(88 citation statements)
references
References 26 publications
2
84
0
2
Order By: Relevance
“…For phosphorene, we show (see Supplementary Material) that its anisotropic mechanical properties [3,36] can only be obtained by considering proper strain-displacement relations. Furthermore, phosphorene is considered to be very interesting from a strain-engineering perspective as it displays a strain dependent band-gap [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…For phosphorene, we show (see Supplementary Material) that its anisotropic mechanical properties [3,36] can only be obtained by considering proper strain-displacement relations. Furthermore, phosphorene is considered to be very interesting from a strain-engineering perspective as it displays a strain dependent band-gap [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…[122] Consequently,these effects render the magnetic properties highly anisotropic,a sb oth diamagnetic and paramagnetic behavior can be observed depending on the orientation in the magnetic field. [138,139] It was recently reported that the Youngsm odulus of few-layer BP was about 58 and 27 GPa in the zigzag and armchair directions,r espectively,w ith highly anisotropic transport behavior in BP and ad erived conductance anisotropy of 63.7 %. 1TPa for graphene).…”
Section: Physical Propertiesmentioning
confidence: 99%
“…Additionally, the intragroup and intergroup angles are, respectively, given by θ 213 = 96.359 ∘ and θ 214 = 102.09 ∘ . In the linear regime, the total strain energy of atom 1 can be expressed as U=12Krr12r1202+12Krr13r1302+12Krr14r1402+12Kθθ213θ21302+12Kθθ214θ21402+12Kθθ314θ31402 where the former three terms describe the VFF potentials steming from the deformations of related bond lengths, and the later three terms parameterize the VFF potentils resulting from the variations of associated bond angles. The parameters K r and K θ are two VFF force constants, and the symbols containing subscript “0” denote the corresponding quantities of a undeformed monolayer BP.…”
Section: Principlementioning
confidence: 99%
“…Additionally, the intragroup and intergroup angles are, respectively, given by θ 213 = 96.359 ∘ and θ 214 = 102.09 ∘ . [21,22] In the linear regime, the total strain energy of atom 1 can be expressed as [23]…”
Section: Principlementioning
confidence: 99%